Environmental Maintenance through the Application of Adat (Criminal) Sanctions on Baduy Communities (Indian Journal of Forensic Medicine & Toxicology, 2021)
This article aims to describe the implementation of customary criminal sanctions used by the Baduycommunity in maintaining and preserving their nature and the effectiveness of the use of customarysanctions in preventing and overcoming actions that damage the environment of the Baduy community. Itis a qualitative research to produce descriptive data, where the approach used is socio-legal research usingsecondary data as a normative or doctrinal approach, and uses a social approach to explore primary data inthe form of values and interpret the behavior of local communities in solving customary cases. The resultsof this study indicate that the life of the Baduy community which is supported by agriculture and cultivationis very dependent on natural preservation. The maintenance and preservation of the environment in theBaduy community is highly respected. Various ways to preserve nature through avoidance of goods andmodern lifestyle are carried out from generation to generation so as not to change the order of nature and theenvironment. In preserving nature, the Baduy community provides guidelines on certain actions that theirindigenous people should not take, such as burning forests, cutting trees in certain areas.
Keywords: Environmental Maintenance, Baduy Communities, Customary law, criminal sanctions